1991
DOI: 10.1111/j.1365-2044.1991.tb11491.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind comparison of epidural diamorphine and intramuscular morphine after elective Caesarean section, with computerised analysis of continuous pulse oximetry

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The median dose of i.m. morphine required by patients in the diamorphine group was 0 mg. Stevens et al (5), who gave 3 mg of epidural diamorphine after caesarean section identified a mean morphine dose requirement of 18 mg; compared with our study, this suggests that there are advantages both in giving a larger dose of epidural diamorphine, and in administering epidural opioids at the time of surgery. I n the same study it was shown that the mean cumulative i.m.…”
Section: Methadone Diamorphinesupporting
confidence: 58%
See 3 more Smart Citations
“…The median dose of i.m. morphine required by patients in the diamorphine group was 0 mg. Stevens et al (5), who gave 3 mg of epidural diamorphine after caesarean section identified a mean morphine dose requirement of 18 mg; compared with our study, this suggests that there are advantages both in giving a larger dose of epidural diamorphine, and in administering epidural opioids at the time of surgery. I n the same study it was shown that the mean cumulative i.m.…”
Section: Methadone Diamorphinesupporting
confidence: 58%
“…Significant numbers of patients in both groups admitted to pruritis on direct questioning, one patient in each group describing it as severe, as also noted by McGrady et al (2). We disagree with Stevens et al (5) who dismissed pruritis as not being a significant side effect of epidural diamorphine.…”
Section: Methadone Diamorphinementioning
confidence: 51%
See 2 more Smart Citations
“…However, Withington, Patrick & Reynolds (1993) found that heroin causes histamine release as frequently as morphine in patients undergoing low-dose pain treatment. Urinary dys function seems to be of no clinical importance in tolerant subjects as opposed to nontolerant subjects (Stevens et al 1991;Bromage et al 1982a, b).…”
mentioning
confidence: 95%